Utility of the AVISE Connective Tissue Disease test in predicting lupus diagnosis and progression - Maureen McMahon; Emily Liang; Mihaela Taylor (Lupus Science and Medicine)
Background The AVISE Connective Tissue Disease (CTD) test uses autoantibody, erythrocyte-bound C4d (EC4d) and B-cell-bound C4d (BC4d) levels to aid in diagnoses of SLE, other CTDs and fibromyalgia. We evaluated the utility of the AVISE CTD test in predicting SLE disease development and damage progression.Methods Patients who had undergone AVISE CTD testing were assessed for SLE diagnosis by the Systemic Lupus International Collaborating Clinics (SLICC) and American College of Rheumatology criteria and for SLE damage by the Systemic Lupus International Collaborating Clinics Damage Index (SDI) at the time of AVISE testing (t=0) and 2 years later (t=2).Results Among 117 patients without a previous diagnosis of SLE, 65% of patients who tested positive developed SLE at t=2, compared with 10.3% of patients who tested non-positive (p<0.0001). AVISE-positive patients fulfilled significantly more SLICC diagnostic criteria than AVISE-non-positive patients at both t=0 (3.8±2.1 vs 1.9±1.1, p=0.001) and t=2 (4.5±2.2 vs 2.1±1.2, p<0.0001). AVISE-positive patients also had had significantly higher SDI at t=2 (1.9±1.3 vs 1.03±1.3, p=0.01). BC4d levels correlated with the number of SLICC criteria at t=0 (r=0.33, p<0.0001) and t=2 (r=0.34, p<0.0001), as well as SDI at t=0 (r=0.25, p=0.003) and t=2 (r=0.26, p=0.002).Conclusions The AVISE CTD test can aid in SLE evaluation by predicting SLE disease development and future damage progression.